Affordances, movement dynamics, and a centralized digital communication platform in a networked movement. Issue 12 (10th September 2022) - Lee, Francis L. F.; Liang, Hai; Cheng, Edmund W.; Tang, Gary K. Y.; Yuen, Samson
ABSTRACT: Much contemporary social mobilization is digitally enabled. Digital media may provide the communication platforms on which supporters deliberate movement goals, share information, discuss tactics, and generate discourses in response to ongoing happenings. Yet digital media's capability to serve these functions should depend on platform-specific affordances and movement dynamics. Based on such premises, this article examines how the online forum LIHKG became the central communication platform in the Anti-Extradition Bill Movement in Hong Kong. Empirically, digital media and content analysis data help establish the forum's prominence during the first few months of the movement, while analyses of protest onsite survey data show how the use of LIHKG systematically related to several movement-related attitudes among the protesters. The article highlights the affordances and movement dynamics that allow the forum to play the role. It contributes to understanding the factors that shape the role and impact of digital media platforms in social mobilization.